التسبيب المعيب للأحكام القضائية (دراسة مقارنة وفقاً لأحكام القضاء الليبي والمصري) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The reasons on which judicial rulings are based are considered as one of the pillars of the factual and legal ruling, and sufficient reasoning is achieved when the causation achieves the purpose of its existence. However, the judicial judgment may be affected by a defect in the formal conditions required by the law. This is represented in the total objective conditions required by law for the issuance of judicial rulings for the defect of deficiencies in factual reasons or the defect of corruption in reasoning, which makes it defective with a defect that may lead to its invalidity due to a deficiency in factual reasons or make it tainted by the defect of error in law due to a deficiency in legal reasons, or partial absence of factual reasons and may be followed by a defect. The causing is important as a guarantee against arbitrariness issued by judges and failure to comply with it leads to defective judicial  rulings whether in terms of reality or in terms of law. This topic was dealt with according to the comparative analytical approach and it was concluded that the effect of not taking reasoning into consideration has a negative impact on the litigants, which leads to the fact that they lose their confidence in judiciary.
Keywords: defective causation; total lack of causes; partial lack of causes; insufficiency of causes